Firefighter Stress and Mental Health: Introduction to the Special Issue. Issue 2 (March 2022) - Van Hasselt, Vincent B.; Bourke, Michael L.; Schuhmann, Bailee B.
The past decade has witnessed burgeoning interest and concern regarding the mental health of firefighters. This increased attention is due, in part, to research documenting higher rates of psychiatric problems, including depression, substance abuse, sleep disturbances, posttraumatic stress disorder, and suicidality in fire rescue personnel compared to civilians. Similarly, the National Institute for Occupation Safety and Health (2014) has identified disturbingly elevated rates of physical health difficulties in firefighters, most notably high blood pressure, coronary heart disease, death due heart attacks, as well as different forms of cancer. Despite the heightened awareness of the mental and physical health challenges in this population, behavioral research specifically targeting firefighters is limited. With this is mind, we asked prominent researchers and clinicians working in this area to present results of their early investigative efforts in our Special Issue on "First Responder Stress and Mental Health". In this Introduction, we provide brief summaries of the studies comprising the Issue. Articles in this issue address topics of sleep, PTSD, substance use, physical health concerns, and provide assessment and treatment considerations. A primary goal of the Issue is to stimulate further behavioral research with this group of deserving yet underserved first responders. Moreover, the Issue serves as a tribute to the men and women of the fire service who dedicate and risk their lives to serve their community.